2021
DOI: 10.3390/su13020978
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Sustainable Framework in STEM Intensive Programs for Secondary and Tertiary Education

Abstract: Sustainability of learning environments is a key pillar of all societal development frameworks. A variety of research address the development of education as a fine balanced relation between flexibility, adaptability, innovation, and efficient resource allocation. The main limitation of current approaches is the lack of correlation between various efficiency analyses and budget expenditure of learning environments. The current research aims at undertaking a comparative evaluation of a sustainable framework in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…(para. 6) Although STEM education should have more innovative and, indeed, more anticipatory roles in identifying global grand challenges and should be future-oriented, it is difficult—and sometimes impossible—for STEM teachers to forecast global grand challenges and translate forecasting results into workable capstone projects that require Future Studies (FS) concepts, methodologies, tools, methods, and skills (Tanenbaum et al, 2016 ). The competencies that STEM teachers must obtain are future-scaffolding STEM competencies relevant to STEM related disciplines, which will empower students to think creatively about the future (Levrini et al, 2019 ).…”
Section: Global Grand Challenges Sustainable Development and Future S...mentioning
confidence: 99%
“…(para. 6) Although STEM education should have more innovative and, indeed, more anticipatory roles in identifying global grand challenges and should be future-oriented, it is difficult—and sometimes impossible—for STEM teachers to forecast global grand challenges and translate forecasting results into workable capstone projects that require Future Studies (FS) concepts, methodologies, tools, methods, and skills (Tanenbaum et al, 2016 ). The competencies that STEM teachers must obtain are future-scaffolding STEM competencies relevant to STEM related disciplines, which will empower students to think creatively about the future (Levrini et al, 2019 ).…”
Section: Global Grand Challenges Sustainable Development and Future S...mentioning
confidence: 99%
“…Meanwhile, sustainable STEM education echoes the aforementioned needs. Today, the movement in higher education integrates reformed knowledge, innovation, and practice while considering the humanities, ethical issues, social learning, and civic engagement with a learning process that is exploratory, action-oriented, reflective, and transformative [21]. While the curriculum has been rapidly reformed at the primary and middle school levels toward STEM, the movement has prompted higher education to change and make their ways of teaching more multifaceted [22].…”
Section: The Role Of Stem Education In Higher Educationmentioning
confidence: 99%
“…Furthermore, the vast majority of existing SET studies use Likert-scale responses to capture student feedback, yet, by its very nature, the response to a close-ended question cannot provide as detailed and as in-depth information as that to an open-ended question [16][17][18] and may sometimes result in an ambiguous finding [19]. For example, one study that aimed to analyze student responses to the NSS 2005/07 open-ended questions [20] revealed that the most frequent issue raised in students' free-text responses pertains to the 'Overall quality of teaching', reporting that the NSS's open-ended questions help to improve the overall response rate.…”
Section: Introductionmentioning
confidence: 99%